Impact of Elaeidobius kamerunicus faust introduction on oil palm fruit formation in Malaysia and factors affecting its pollination efficiency: a review - Mohamad, Saharul Abillah (Lembaga Minyak Sawit Malaysia, 2022)
The oil palm pollinating weevil, Elaeidobius kamerunicus, has become the single most important insect pollinator of the commodity crop in Malaysia and Indonesia, 40 years after its introduction. However, in 2020, the average national oil extraction rate (OER) has decreased from 20.21% to 19.92%. The decline was attributed to the lower oil palm fruit bunch quality. This has raised concerns on the pollination efficiency of the pollinator. As such, the factors affecting the pollination efficiency of E. kamerunicus were thoroughly discussed in this review. Eight factors, which were categorised into intrinsic and extrinsic factors, were discussed in detail. Intrinsic factors discussed are the genetic make-up of E. kamerunicus and its population level. Meanwhile, factors such as planting materials, soil types, plant physiological condition, volatiles emission, diseases/predators threatening E. kamerunicus and climatic factors were discussed in the extrinsic factors. Methods for maintaining a healthy pollinator population were suggested, as well as an emphasis on future studies based on the shortlisted factors.